Development of edm tool for producing titanium alloy automotive valve application - Muhammad Syauqi, Shaidan (2013)
This paper presents the development of EDM tool for producing titanium alloy automotive valve application. Electric discharge machining (EDM) is a non-traditional machining processes that involved a transient spark discharges through the fluid due to the potential difference between the electrode and the work piece. The objective of this paper is to investigate how the peak current, servo voltage, pulse on- and off-time in EDM effect on Material Removal Rate (MRR), Tool Wear Rate (TWR). The experimental control parameters were being optimized according to their various machining characteristics namely Material Removal Rate (MRR), Tool Wear Rate (TWR) using copper as the electrode and also copper as the workpiece. Design of experiment (DOE) technique is used to determine the optimum machining parameters for this machining characteristic. Taguchi method has been used for the construction, layout and analysis of the experiment for MRR and TWR machining characteristic. The use of Taguchi method in the experiment saves a lot of time and cost of preparing and machining the experiment samples. Therefore, an L9 Orthogonal array which was the fundamental component in the statistical design of experiments has been used to plan the experiments, Analysis of Variance (ANOVA) is used to determine the optimum machining parameters for this machining characteristic. The result shown the peak current are most significant factor that affect material removal rate(MRR) and tool wear ratio (TWR) since the parameter bring major effect to MRR and TWR. As conclusion, the development of EDM tool is achieved and got the optimum parameter for MRR and TWR.